Mechanistic Parameters of Electrocatalytic Water Oxidation on LiMn2O4 in Comparison to Natural Photosynthesis. Issue 22 (27th October 2017) - Köhler, Lennart; Ebrahimizadeh Abrishami, Majid; Roddatis, Vladimir; Geppert, Janis; Risch, Marcel
Abstract: Targeted improvement of the low efficiency of water oxidation during the oxygen evolution reaction (OER) is severely hindered by insufficient knowledge of the electrocatalytic mechanism on heterogeneous surfaces. We chose LiMn2 O4 as a model system for mechanistic investigations as it shares the cubane structure with the active site of photosystem II and the valence of Mn 3.5+ with the dark‐stable S1 state in the mechanism of natural photosynthesis. The investigated LiMn2 O4 nanoparticles are electrochemically stable in NaOH electrolytes and show respectable activity in any of the main metrics. At low overpotential, the key mechanistic parameters of Tafel slope, Nernst slope, and reaction order have constant values on the RHE scale of 62(1) mV dec −1, 1(1) mV pH −1, −0.04(2), respectively. These values are interpreted in the context of the well‐studied mechanism of natural photosynthesis. The uncovered difference in the reaction sequence is important for the design of efficient bio‐inspired electrocatalysts. Abstract : Natural vs. artificial : We elucidate the key parameters of the electrocatalytic mechanism of water oxidation on LiMn2 O4 and interpret the values in the context of natural photosynthesis. The uncovered differences are important for the design of more efficient bio‐inspired electrocatalysts.